Carbon Emissions Peak in the Road and Marine Transportation Sectors in View of Cost-Benefit Analysis: A Case of Guangdong Province in China - Zhao, Yongming; Ding, Hui; Lin, Xiaofang; Li, Li; Liao, Wenyuan; Liu, Yonghong (Frontiers in Environmental Science, 2021)
The road and marine transportation sectors have attracted a great deal of attention as one of the main sources of carbon emissions. In this study, a LEAP (long-range energy alternatives planning system) model is used to predict the energy demand and carbon emissions of the road and marine transportation sectors in Guangdong Province from 2016 to 2030. Based on the model results, if Guangdong Province does not adopt new control measures, in 2030, the energy demand and CO2 (carbon dioxide) emissions from the road and marine transportation sectors will have increased by 117% and 116% respectively, compared to the levels in 2015. Conversely, under a low-carbon scenario, carbon emissions will peak by 2027 in Guangdong Province. Motor vehicle control measures generate the strongest reduction in energy consumption and CO2 emissions for the road and marine transportation sectors in Guangdong Province. Furthermore, the reduction of emissions resulting from these measures would increase over time. Public transportation development and the promotion of clean energy measures also play significant roles in reducing carbon emissions long-term. The contribution of road passenger transport to emission reduction is the largest, followed by marine freight transport and road freight transport. While the energy demand and carbon emissions peak at a similar time in the model, the peak time for CO2 occurs slightly earlier.